2021
DOI: 10.3233/bmr-200147
|View full text |Cite
|
Sign up to set email alerts
|

Comparative efficacy of 12 non-drug interventions on non-specific chronic low back pain in nurses: A systematic review and network meta-analysis

Abstract: BACKGROUND: Many non-drug interventions for decreasing non-specific chronic low back pain (NSCLBP) in nurses have been extensively studied, but the most effective approach is still unclear. OBJECTIVE: This systematic review and network meta-analysis evaluated the efficacies of 12 non-drug interventions in reducing NSCLBP in nurses. METHODS: PubMed, ScienceDirect, Web of Science, Cochrane, EMBASE, CINAHL, Medline, WANFANG, VIP, China Knowledge Integrated, and SinoMed were searched from their establishment to Ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 54 publications
1
4
0
Order By: Relevance
“…Our findings further revealed that a higher education level was positively correlated with NSAIDs efficacy, compared to the negative factors of nociceptive and affective conditions that decrease the likelihood of response to NSAIDs. This is in line with a previous study in which patients with higher education levels performed better adherence by self-management strategies and improvement of their life quality ( Sun et al, 2021 ). However, the prevalence of migraine was higher among women and less educated people, and a third of patients do not consider migraine as a disease ( Brusa et al, 2019 ).…”
Section: Discussionsupporting
confidence: 93%
“…Our findings further revealed that a higher education level was positively correlated with NSAIDs efficacy, compared to the negative factors of nociceptive and affective conditions that decrease the likelihood of response to NSAIDs. This is in line with a previous study in which patients with higher education levels performed better adherence by self-management strategies and improvement of their life quality ( Sun et al, 2021 ). However, the prevalence of migraine was higher among women and less educated people, and a third of patients do not consider migraine as a disease ( Brusa et al, 2019 ).…”
Section: Discussionsupporting
confidence: 93%
“…Another systematic review identified, based on their network meta-analyses, that low back exercises plus health education were the most effective procedures on the effects of non-drug intervention management in nurses, followed by single low back exercise intervention and yoga [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…In relation to the NMAs that also included psychological interventions, aimed at reducing pain related distress and functional disability by changing patients’ negative beliefs, behaviors and attitudes through a combination of principles and strategies informed by psychological theories, pain education and cognitive–behavioral therapy stand out as the most effective treatments, but they all agree that these interventions are more effective when carried out in conjunction with physical therapy programs (mainly structured therapeutic exercise) [ 71 , 72 , 73 ]. These results are in line with the intervention that produced the best effect for both pain intensity and functional disability in our study, a multimodal intervention that addresses cognitive, behavioral and physical aspects.…”
Section: Discussionmentioning
confidence: 99%